PENGEMBANGAN BAHAN AJAR MODUL UNTUK MENINGKATKAN MOTIVASI BELAJAR MATEMATIKA EKONOMI - Ridaul Innayah; Hendra Purwanto; Handaru Indrian S. Adi (Promosi: Jurnal Program Studi Pendidikan Ekonomi, 2024)
This research is to find out about: The influence of the module on student learning motivation in economic math courses, and Differences in learning motivation among students who use modules and PowerPoint (conventional). This research data was collected using closed questionnaires and questions to determine student responses regarding the use of modules, especially in experimental classes. And then analyzed it using t- test to determine the differences in student learning motivation before and after using module. From the results of statistical tests, it is known that the significance value is 0.000 and the tcount is 4.141, indicating a significant positive influence from the use of modules in learning economic mathematics. And it can be seen that the average value of learning motivation in the experimental class is higher than in the control class, namely 112.94 and 84.65 respectively. Based on the research findings, it can be concluded: The module has a positive effect on student learning motivation in the economic math course, and there are differences in learning motivation in students who use modules compared to PowerPoint (conventional) in economic math courses.Â Keywords: economic math; module; motivation to learn; and teaching materials.